2013
DOI: 10.1016/j.smrv.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing and reconstructing cognitive performance in sleep deprivation

Abstract: Summary Mitigation of cognitive impairment due to sleep deprivation in operational settings is critical for safety and productivity. Achievements in this area are hampered by limited knowledge about the effects of sleep loss on actual job tasks. Sleep deprivation has different effects on different cognitive performance tasks, but the mechanisms behind this task-specificity are poorly understood. In this context it is important to recognize that cognitive performance is not a unitary process, but involves a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 101 publications
(126 reference statements)
2
94
0
Order By: Relevance
“…Even though the association between sleepiness and IGT performance was not evident using the coarse metric of net score, changes in underlying cognitive processes were found when task performance was examined using the EV model. By breaking down the IGT into underlying component processes, this study begins to address the "task impurity problem" (Jackson et al, 2013) that has posed a challenge to research in cognitive effects of sleep deprivation , and joins a growing body of literature demonstrating that mathematical modeling can elucidate multiple factors underlying task performance during sleep loss (Ratcliff & Van Dongen, 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the association between sleepiness and IGT performance was not evident using the coarse metric of net score, changes in underlying cognitive processes were found when task performance was examined using the EV model. By breaking down the IGT into underlying component processes, this study begins to address the "task impurity problem" (Jackson et al, 2013) that has posed a challenge to research in cognitive effects of sleep deprivation , and joins a growing body of literature demonstrating that mathematical modeling can elucidate multiple factors underlying task performance during sleep loss (Ratcliff & Van Dongen, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep deprivation results in performance decrements on tasks measuring various aspects of executive functioning, including response inhibition (Drummond, Paulus, & Tapert, 2006;Harrison, Jones, & Waterhouse, 2007), working memory (Groeger et al, 2008), resistance to distracting information ("filtering efficiency"; Drummond, Anderson, Straus, Vogel, & Perez, 2012), planning (Killgore, Kahn-Greene, Grugle, Killgore, & Balkin, 2009), and judgment/moral reasoning (Olsen, Pallesen, & Espevik, 2013). While deficits on complex executive functioning and decision-making tasks have been identified (Killgore, Balkin, & Wesensten, 2006;Killgore, Grugle, & Balkin, 2012;Killgore, Lipizzi, Kamimori, & Balkin, 2007), it is unclear whether these are related to specific disturbances in executive functioning or to more basic underlying cognitive processes such as sustained attention that also contribute to overall performance on these tasks (Jackson et al, 2013;Tucker, Whitney, Belenky, Hinson, & Van Dongen, 2010).…”
mentioning
confidence: 99%
“…1 In laboratory studies, sleep deprivation has consistently been shown to substantially degrade vigilance and sustained attention, whereas its effects on demanding tests of complex cognition such as decision making appear to be inconsistent and relatively small. 2,3 Paradoxically, in the natural environment there are well-documented deficits in decision making due to sleep deprivation.…”
mentioning
confidence: 99%
“…Furthermore, computational modelling in cognitive architectures has been employed to simulate sleep-deprived cognitive performance on the basis of the constituent cognitive processes. These efforts are beginning to enable quantitative prediction of the effects of sleep deprivation to be made across different task contexts [19].…”
Section: The Pathophysiology Of Drivingmentioning
confidence: 99%